Development of maintenance cost correlation for high head run of river small hydro power plant. Issue 1 (31st December 2022) - Kumar, Ravi; Singal, S.K.; Dwivedi, Gaurav; Shukla, Anoop Kumar
Abstract : Small hydropower is a mature and cost-competitive energy technology. The maintenance cost of small hydropower plant is one of the critical factors to analyse the net benefits of the plant. In this study, an attempt has been made to develop the maintenance cost correlation for the high head run of river small hydropower plants based on capacity and head as cost-influencing parameters by linear regression approach in MATLAB. The results revealed that the maximum deviation is ±12.60%, the maximum average deviation cost obtained for turbine is ±11.35% and minimum average deviation cost for thrust bearing is ±3.5%. Overall average deviation in maintenance cost of all the studied components is ±7.35%, which shows that the developed correlations are in good agreement. Therefore, these correlations can be used to determine the maintenance cost of high head run of river small hydropower projects.